2020
DOI: 10.21577/0100-4042.20170520
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL AND BIOLOGICAL STUDIES OF CONSTITUENTS FROM ROOTS OF Salacia crassifolia (CELASTRACEAE)

Abstract: Salacia crassifolia traditionally known as "Bacupari-do-Cerrado" is used to treat kidney problems, and as a healing agent for coughs and malaria. The phytochemical study of the S. crassifolia roots led to the isolation of thirteen compounds: abruslactone-A (1), urs-12-ene-3β,25,30-triol (2), carioprystimerin (3), β-sitosterol (4), pristimerin (5), dispermoquinone (6), netzahualcoyonol (7), 20-hydroxy-20-epi-tingenone (8), 6-oxo-pristimerol (9), 9β,10β-epoxi-3β-hydroxy-1βH,4βH,5βH,7βH,11αH-guaian-12,8β-olide (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Pristimerin is the major metabolite isolated from hexane/ethyl ether extract of Salacia crassifolia roots, being obtained 5 g, equivalent to 10% of the crude extract (Dos Santos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pristimerin is the major metabolite isolated from hexane/ethyl ether extract of Salacia crassifolia roots, being obtained 5 g, equivalent to 10% of the crude extract (Dos Santos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The earliest compounds described for this class are celastrol and pristimerin (Figure 1), which have been isolated from Tripterygium wilfordii Hook, Celastrus scandens L. and Pristimera indica (Gunatilaka, 1996). And, in 2020, Dos Santos and collaborators isolated pristimerin from hexane/ethyl ether extract obtained from roots of Salacia crassifolia in a significant amount (5 g), constituting the main compound of this extract (10%) (Dos Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest compounds described for this class are celastrol and pristimerin (Figure 1), which have been isolated from Tripterygium wilfordii Hook, Celastrus scandens L. and Pristimera indica (Gunatilaka, 1996). In this study, pristimerin was isolated from the hexane/ethyl ether extract of Salacia crassifolia roots in a significant amount (5 g), constituting the major compound of this extract (10%) (Dos Santos et al, 2020). Source: Author's own.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above and the significant amount of isolated pristimerin from Salacia crassifolia G.Don., a plant of the family Celastraceae (Dos Santos et al, 2020), the synthetic route shown in Figure 4 was proposed to obtain a trimer of pristimerin. The units of pristimerin with azidic oligoethyleneglycol spacer would be introduced in the branched trialkyne by means of click chemistry.…”
Section: Introductionmentioning
confidence: 99%